Regional economic cycles and the emergence of sheltered economies in the periphery of the EU - Andres Rodríguez-Pose; Ugo Fratesi (European Regional Science Association (ERSA), 2003)
It has been claimed that in recent years the evolution of regional disparities within European nations has become pro-cyclical, that is, disparities tend to increase in times of economic boom and to decrease during recessions. This represents a change with respect to the traditional patterns in the 1960s and 1970s, when growth in European lagging regions was higher than in the core during periods of economic growth, but lagging regions were more affected by economic crises. In this paper we first assess where and when this change has happened and then analyse what are the factors behind the change in the evolution of disparities. We use a 20-year long database, comprising NUTS II regions in five European countries (France, Greece, Italy, Portugal and Spain) which include the great majority of European lagging regions. The evidence supports the shift to pro-cyclical patterns in the evolution of regional disparities, especially in those countries with a large number of Objective 1 regions (Spain, Italy and, less clearly, in Greece) whereas in France such a change has not yet occurred. Looking for the determinants of regional economic cycles, we conduct regression analyses finding that the shift in growth patterns is related to the emergence of what is known as sheltered economies, i.e. economies that are increasingly detached from the market, and thus increasingly impervious to economic cycles. Lagging European regions have become over the period of analysis increasingly dependant on factors such as transfers, public investment, and public employment and therefore less exposed to changes in market conditions.
Keywords: 330